(untitled) (Teacher’s World: Journal of Education and Research, 2024)
The efficient execution of educational programs in schools has made the position of educational administrators increasingly important. Theories offer a conceptual structure that facilitates comprehending, forecasting, and managing behavior within organizational settings. The purpose of this study is to explore the practice of educational administration (EA) theories in secondary school of Bangladesh, and the role of educational administrators. A qualitative approach is used for gaining in-depth understanding in the real-life-situation. Semi-Structure Interview and Focus Group Discussion have been used to collect data. Data have been analyzed using thematic analysis technique. Findings show that secondary schools of Bangladesh are practicing the Scientific Management Theory and System Theory collaboratively through maintaining formal structure. Human Relationship and Behavioral Approach Theory have been practiced in the shadow of formal structure. As well a hybrid approach is being practiced in the schools. The administrators find the challenges to practice these theories. The challenges are lack of infrastructure, scarcity of teaching learning resources, teacher-student-ratio, local conflict, and school managing committee’s internal clash. The findings of this study would be useful for educators, educational administrators and researchers in advancing EA theories in education. Teacher’s World: Journal of Education and Res arch, 50(1): 135-154